Cytotoxicity Effect of Hull-Less Seed Pumpkin Extract on Human Papillary Thyroid Cancer Cell Line - Zoleikha Azari; Arash Zamini; Sara Dabirian; Mojtaba Mehrdad; Jamalali Olfati; Ideh Dadgaran; Mohammad Hadi Bahadori (Negah Institute for Scientific Communication, 2020)
Introduction: Thyroid cancer is the most prevalent endocrine malignancy tumor, and its incidence is increasing. Chemotherapy drugs like Paclitaxel (PTX) are a common treatment for cancer; however, they have many adverse effects. Plants are a source of anticancer agents. The present study assessed the cytotoxic effects of hydro-alcoholic extract in comparison with those of paclitaxel on Papillary Thyroid Cancer (PTC) cell line. Methods: PTC cell line was treated by different concentrations of extract and paclitaxel for 24, 48, and 72 h. Cytotoxicity was examined through Trypan blue and clonogenic assays. Acridine Orange/Ethidium Bromide (AO/EB) staining was used for detecting apoptotic cells. The observations were statistically tabulated and analyzed.  Results: The Trypan blue staining results suggested that hydro-alcoholic extract had a cytotoxic effect on PTC cells. Our results of AO/EB staining revealed that the hydro-alcoholic extract of Hull-Less Seed Pumpkin (HLSP) in the concentration of ≥100 μl/mL induced significant apoptosis in the PTC cultured cell (P<0.05). In addition, the AO/EB staining data suggested an increase in the number of apoptotic cells with increasing the concentration of extract and paclitaxel. The clonogenic assay results indicated a decrease in colonies by increasing the concentration. Comparing the groups treated by paclitaxel or HLSP extract, with the control group revealed significant differences between them (P<0.05). Conclusion: The HLSP extract had a cytotoxic effect on the human PTC cell line. Based on the adverse effects of chemotherapy drugs, this extract can be considered as a beneficial agent for PTC treatment.